A Reevaluation of the Association Between Instrument Delivery and Epidural Analgesia. Issue 1 (January 1995) - Hawkins, Joy L.; Hess, Kenneth R.; Kubicek, Martha A.; Joyce, Thomas H.; Morrow, Dean H.
Abstract : Background and Objectives: Over 100 papers in the medical literature suggest pro or con that epidural analgesia is associated with an increase in the incidence of instrument delivery. This two-component study was performed to evaluate the influence of epidural labor analgesia on the incidence of instrument delivery. Methods: Component 1 was a retrospective analysis of the medical records of 14, 804 mothers having a vaginal delivery before and after implementation of an active epidural service. Component 2 was a case control study designed to determine factors, in addition to epidural analgesia, associated with an increase in instrument delivery. In component 2 11 factors describing maternal, fetal, anesthetic, and obstetric factors were analyzed for each of 609 consecutive patients having an instrument delivery and 246 controls having a spontaneous vaginal delivery. Results: In component 1, despite a tenfold increase in the use of epidural analgesia, there was a similar association between epidural use and instrument delivery in both time periods. Additionally, the epidural-forceps association was twice as strong for parous patients as for nulliparous patients (odds-ratios 9.74 and 4.52, respectively). In component 2, five factors were significantly ( P > .0001) associated with instrument delivery conclusions. Conclusions: While epidural analgesia was one factor, the others were gestational age >41 weeks, a second stage of labor >2 hours, an occiput posterior or transverse fetal position, and previous cesarean section. These four factors are individually and independently associated with an increase in the incidence of instrument delivery independent of epidural use.